Cyberlaw for global E-business finance, payments, and dispute resolution - Kubota, Takashi; IGI eBooks; IGI Global (Hershey, Pa. : IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2008)
This book examines cyberlaw discussions worldwide on topics such as cybercrime and risk management, comparative electronic trading systems of securities, digital currency regulation, jurisdiction and consumer protection in cross-border markets, and case law on international bank transfers. An invaluable resource for policy-makers, business experts, lawyers, scholars, and researchers, this book provides comprehensive research from a global perspective on the legal, technical, and financial implications of e-business.
1. Cybercrime, cybersecurity, and financial institutions worldwide / Pauline Reich -- 2. Enhancing cyber risk management with the framework of ERM and Basel II / Junji Hiwatashi -- 3. IT development and the separation of banking and commerce / Takashi Kubota -- 4. Laws and regulations on Proprietary Trading System (PTS) in Japan / Motoaki Tazawa -- 5. The holding and transfer of interests in securities in England and Japan / Tomonori Fujiike -- 6. Global trends of payment systems and the next-generation RTGS Project in Japan / Masaaki Nakajima -- 7. Technical and legal concerns about global card payments / Fernando Barrio -- 8. The regulation of new forms of electronic fund transfers in Japan focusing on electronic money / Takashi Nakazaki -- 9. Commodity based digital currency / Evelyn Meow Hoong -- 10. Mistakes in remittance to account / Masao Yanaga -- 11. Doing international business online for the small and medium enterprise / Sam Edwards -- 12. Consumer protection in cross-border e-commerce markets / Shino Uenuma -- 13. Cyber contract and Indian law / Jibitesh Mishra, Biswajit Tripathy -- 14. E-commerce and dispute resolution / Naoshi Takasugi -- 15. Cross-border court jurisdiction and economic law application in electronic commerce / Takeshi Kawana.
Includes bibliographical references (p. 272-286) and index.
Also available in print.
Mode of access: World Wide Web.
Title from PDF t.p. (viewed on June 5, 2010).
Keywords: Electronic commerce -- Law and legislation; Computer crimes; Electronic trading of securities -- Law and legislation; Electronic commerce -- Law and legislation -- Japan; Commodity-based digital currency; Consumer protection in e-commerce markets; Cross-border jurisdiction; Cyber contract; Cyber risk management; Cybercrime and cybersecurity; Dispute resolution; Electronic money; Global trends in payment systems; Holding and transfer of interests; IT development in finance; Laws and regulations in e-commerce; Mistakes in remittance to account; Online business for small to medium enterprises; Proprietary trading system; Regulation of electronic fund transfers; Separation of banking and commerce; Technical and legal concerns about global card payments; Electronic books